Development of Technical Textile for Packtech Production Using Jute Fibres - Omolale, A. B.; Emidun, E. B. (NIU Journal of Humanities; Vol. 8 Núm. 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
Jute is a natural renewable fibrous biomass that has long been used as a raw material in the manufacture of packaging items. It resembles both cotton and wood. It features a diversified fibre with soft and firm fibre properties. A diverse range of vertical and horizontal environmentally friendly products can be manufactured using its biodegradable, photodegradable, thermally degradable, high strength, non-plastic, nontoxic, high-water and ultraviolet-absorbing capacities, visco-electricity, and crystalline cellulosic properties. Its extra geotextile and technical textile potential is represented by its porosity, permeability, capillarity, and hydraulic characteristics. Crystalline hardness and brittleness, on the other hand, are particularly promising for a variety of composite goods that can replace glass, carbon, asbestos, wood, and synthetic composite materials. The purpose of this study is to investigate the environmentally beneficial features and applications of Jute products in a modern era where people are unduly dependant on nondegradable plastic materials (Petrochemical products). Jute products are not only environmentally friendly and help to decrease soil climatic deterioration. As rapid climate change and global warming have become a major concern and challenge for sustainable and eco-friendly development in the twenty-first century, the reduction of carbon footprint, water footprint in buildings/constructions, and green technology is currently gaining global attention (Abdullah & Rahman, 2018). Keywords: fibrous, biomass, packaging, biodegradable, photodegradable, geotextile, technical textile, eco-friendly.